THE URGENCY OF ENFORCING THE TEACHER'S CODE OF ETHICS IN CREATING CHILD-FRIENDLY SCHOOLS IN THE PURWOREJO DISTRICT - Hardiyanti, Marzellina; Budoyo, Sapto; Widodo, Wahyu (Jurnal Meta-Yuridis, 2024)
Children are the nation's next generation with the right to receive a proper education. Educational services are provided by teachers to children as students based on the teacher's duties and responsibilities. Still, violations often occur by teachers and fellow students in the implementation of education in schools, such as bullying, discrimination, or intolerance. The problem in this article is the need to enforce a teacher code of ethics in assisting child-friendly schools in Purworejo Regency and efforts to encourage the optimization of child-friendly schools in Purworejo Regency. This article uses a juridical-empirical approach which utilizes primary data sources and secondary data which is then analyzed using a descriptive-analytical approach. The results and discussion in this article show that Purworejo Regency needs assistance with a teacher's code of ethics in implementing safe home-based schools because in several schools there are still violations by educators and students in terms of bullying and discriminatory acts so that the implementation of child-friendly based schools is not yet ideal. Efforts to create an ideal child-friendly school in Purworejo Regency are by integrating the roles of stakeholders namely teachers, Regional Apparatus Organizations (Education Service), and the Republic of Indonesia Teachers Association (PGRI) in Purworejo Regency so that child-friendly education in Purworejo can be realized optimally.Â Mentoring, Teachers, Child-Friendly Schools.